Does Esophagectomy Provide a Survival Advantage to Patients Aged 80 Years or Older? Analyzing 5066 Patients in the National Database of Hospital-based Cancer Registries in Japan. Issue 1 (29th July 2022) - Motoyama, Satoru; Maeda, Eri; Iijima, Katsunori; Sato, Yusuke; Koizumi, Shigeto; Wakita, Akiyuki; Nagaki, Yushi; Fujita, Hiromu; Yoneya, Takatoshi; Imai, Kazuhiro; Terata, Kaori; Minamiya, Yoshihiro; et al.
Abstract : Objective: To determine whether esophagectomy provides a survival advantage in octogenarians with resectable thoracic esophageal cancer. Summary Background Data: Elderly patients with thoracic esophageal cancer do not always receive the full standard treatment; however, advanced age alone should not preclude the use of effective treatment that could meaningfully improve survival. Methods: We retrieved the 2008 to 2011 data from the National Database of Hospital-based Cancer Registries from the National Cancer Centerin Japan, divided the patients into a ≥75 group (75–79 years; n = 2935) and a ≥80 group (80 years or older; n = 2131), and then compared the patient backgrounds and survival curves. A multivariable Cox proportional hazards regression model was developed to compare the effects of esophagectomy and chemoradiotherapy in the 2 groups. Results: A significantly greater percentage of patients were treated with esoph-agectomy in the ≥75 group (34.6%) than the ≥80 group (18.4%). Among patients who received esophagectomy, the 3-year survival rate was 51.1% in the ≥ 75 group and 39.0% in the ≥80 group ( P < 0.001). However, among patients who received chemoradiotherapy, there was no difference in survival curve between the 2 groups ( P = 0.17). Multivariable Cox proportional hazard analysis revealed that esoph-agectomy for clinical Stage ii-iii patients was significantly associated to better survival (adjusted HR: 0.731) (95%CI: 0.645–0.829, P < 0.001) in the ≥75 group but not the ≥ 80 group when compared with chemoradiotherapy. Conclusions: Many octogenarians do not necessarily get a survival benefit from esophagectomy. However, patients should be evaluated based on their overall health before ruling out surgery based on age alone.